Nanocomposite Coatings on Tribological Application in Automotive Engine - Sathiyaraj, V.; Naveenchandran, P.; Balakrishnan, C. (International Journal of Psychosocial Rehabilitation, 2018)
The structure, hardness, grinding and wear of tungsten nitrides arranged by DC receptive magnetron sputtering were researched. The coatings were stored with various nitrogen to argon proportions; the aggregate weight was kept consistent. The tribological tests were performed on the covered example in earthbound air with SS304 stainless steel. The coatings showed diverse stages as a component of the nitrogen content: movies with low N content displayed the α-W stage; β-W stage was prevailing for nitrogen substance from 7 to 10 at.% and β-W2N was watched for nitrogen content at 15at.%. We report the readiness of tungsten nitride movies developed by receptive sputtering in the encompassing N2/Ar blend at different weights on stainless steel substrates at different constant temperatures. The structural property is analysed using XRD, mechanical properties are evaluated by nano indentation and metallurgical properties by AFM, EDAX in view of the affidavit conditions. The relationship between the microstructure and mechanical properties is talked about. The mechanical and tribological properties of the tungsten nitride coatings were unequivocally affected by the structure. The hardness and the Young’s modulus qualities were in the reaches (27–39GPa) and (239-280GPa), individually; the most minimal qualities compare to the coatings with the most astounding nitrogen content. For the most part, the grating and wear rate of tungsten nitride coatings sliding against fumes gas expanded with nitrogen content achieving a greatest at 12 at.%; additionally increment of the nitrogen content prompted to a reduction of the erosion and wear.